PENGARUH PROFITABILITAS, LEVERAGE, STRUKTUR MODAL DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN OTOMOTIF YANG TERDAFTAR DI BURSA EFEK INDONESIA - Mar’ah, Saadatul; Damayanti (JURNAL EKONOMI, 2023)
The research conducted aims to prove the effect of profitability, leverage, capital structure and company size on company value in automotive companies listed on the Indonesia Stock Exchange. The population used in the research was conducted using automotive companies listed on the Indonesian Stock Exchange. The sample selection technique uses purposive sampling. The sample used in this research is automotive companies listed on the Indonesia Stock Exchange in 2017-2021, with a sample of 12 companies. Data analysis technique using multiple linear regression analysis. The results of the research conducted show that the independent variables of profitability and leverage have no significant positive effect on company value in automotive companies listed on the Indonesia Stock Exchange. Meanwhile, the independent variables of capital structure and company size have no significant negative effect on firm value in automotive companies listed on the Indonesia Stock Exchange. The value of Adjusted R2 is 0.057%, or this means that the independent variables namely profitability, leverage, capital structure, and company size in this regression are able to explain the dependent variable, namely firm value of 5.7% while the remaining 94.3% is explained by the variable others that were not examined in this study.